Eksistensi Industri Eggroll Waluh Terhadap Kondisi Sosial Ekonomi Masyarakat Desa Ngroto Kecamatan Cepu Kabupaten Blora - Melati, Beuty Rosa; Hayati, Rahma (Edu Geography, 2021)
The existence of the waluh eggroll industry is located in Ngroto Village, Cepu District, Blora Regency, which uses waluh as a food ingredient for superior products. This study aims to determine the development of the industry, the marketing strategy for industrial products, and the influence of the eggroll industry's existence on the socio-economic conditions of society. Using the exploratory sequential model combination method. In answering the first and second problem formulations using a qualitative approach. Data analysis techniques include data collection, data reduction, data presentation, drawing conclusions. In the third problem formulation using a quantitative approach. Methods of data collection using observation, questionnaires, documentation, and interviews. In the analysis using simple linear regression test. The development of the eggroll waluh industry from its inception until now has continued to spread in various regions, known as Cepu souvenirs. Marketing strategy uses product, price, distribution and promotion strategies. The existence of the eggroll waluh industry affects the socio-economic conditions of the people of Ngroto Village. It can be proven by a simple linear regression test, the regression equation is Y = 21.943 + 0.600 X. The t test hypothesis is obtained tcount = 5.734> t table = 1.990. So that the answer to the research hypothesis is that Ho is rejected and Ha is accepted. Eksistensi industri eggroll waluh berlokasi di Desa Ngroto Kecamatan Cepu Kabupaten Blora, yang memanfaatkan waluh sebagai bahan makanan produk unggulan. Penelitian ini bertujuan untuk mengetahui perkembangan industri, strategi pemasaran produk industri, dan pengaruh eksistensi industri eggroll waluh terhadap kondisi sosial ekonomi masyarakat. Menggunakan metode kombinasi model sekuensial eksploratoris. Dalam menjawab rumusan masalah pertama dan kedua menggunakan pendekatan kualitatif. Teknik analisis data mencakup pengumpulan data, reduksi data, penyajian data, penarikan kesimpulan. Pada rumusan masalah ketiga menggunakan pendekatan kuantitatif. Metode pengumpulan data menggunakan observasi, angket, dokumentasi, dan wawancara. Di analisis menggunakan uji regresi linear sederhana. Perkembangan industri eggroll waluh dari awal berdiri sampai sekarang terus berkembang menyebar diberbagai daerah, yang dikenal sebagai oleh-oleh khas Cepu. Strategi pemasaran menggunakan strategi produk, harga, distribusi, dan promosi. Eksistensi industri eggroll waluh berpengaruh terhadap kondisi sosial ekonomi masyarakat Desa Ngroto. Dapat dibuktikan dengan uji regresi linear sederhana didapat persamaan regresi Y = 21,943 + 0,600 X. Hipotesis uji t didapat thitung = 5,734 > ttabel = 1,990. Sehingga terjawabnya hipotetsis penelitian yaitu Ho ditolak dan Ha diterima.